Autism spectrum disorder in the scope of tactile processing. (January 2018) - Mikkelsen, Mark; Wodka, Ericka L.; Mostofsky, Stewart H.; Puts, Nicolaas A.J.
Highlights: A thorough review of tactile assessments in autism spectrum disorder (ASD). A focus on clinical and behavioral assessments in ASD. Discussion of links to neurophysiological mechanisms. Critical assessments of the missing links in this research area. Abstract: Sensory processing abnormalities are among the most common behavioral phenotypes seen in autism spectrum disorder (ASD), typically characterized by either over- or under-responsiveness to stimulation. In this review, we focus on tactile processing dysfunction in ASD. We firstly review clinical studies wherein sensitivity to tactile stimuli has traditionally been assessed by self-, parent- and experimenter-reports. We also discuss recent investigations using psychophysical paradigms that gauge individual tactile thresholds. These more experimentally rigorous studies allow for more objective assessments of tactile abnormalities in ASD. However, little is understood about the neurobiological mechanisms underlying these abnormalities, or the link between tactile abnormalities and ASD symptoms. Neurobiological research that has been conducted has pointed toward dysfunction in the excitation/inhibition balance of the central nervous system of those with ASD. This review covers recent efforts that have investigated tactile dysfunction in ASD from clinical and behavioral perspectives, and some of the efforts to link these to neurobiology. On the whole, findings are inconsistent, which can be ascribed to the subjectivity of clinical assessments, the heterogeneity of ASD cohorts, and the diversity of tactile sensitivity measures. Future endeavors into understanding tactile processing differences in ASD will greatly benefit from controlled experiments driven by neurobiological hypotheses.